2020
DOI: 10.1371/journal.pone.0237783
|View full text |Cite
|
Sign up to set email alerts
|

Eutectic mixture of local anaesthetics for pain reduction during extracorporeal shockwave lithotripsy: A systematic review and meta-analysis

Abstract: A systematic review and meta-analysis was conducted to explore the effect of a eutectic mixture of local anaesthetics (EMLA) on pain reduction during extracorporeal shockwave lithotripsy (ESWL). PubMed, Web of Science, Embase, EBSCO, and Cochrane library databases (updated March 2020) were searched for randomised controlled trials (RCTs) assessing the effect of EMLA for patients that underwent ESWL. The search strategy and study selection process were managed according to the PRISMA statement. Six RCTs were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…For pain relief, previous studies have suggested the use of topical anesthetic creams such as EMLA (6), which can penetrate the skin to a depth of 4 mm. However, the analgesic effect of topical anesthetics did not reduce the need for analgesia as shown in previous RCT (60) and meta-analysis (61). The result may be explained by the inadequacy of topical anesthesia to alleviate both deep somatic pain and visceral pain (62).…”
Section: Discussionmentioning
confidence: 64%
“…For pain relief, previous studies have suggested the use of topical anesthetic creams such as EMLA (6), which can penetrate the skin to a depth of 4 mm. However, the analgesic effect of topical anesthetics did not reduce the need for analgesia as shown in previous RCT (60) and meta-analysis (61). The result may be explained by the inadequacy of topical anesthesia to alleviate both deep somatic pain and visceral pain (62).…”
Section: Discussionmentioning
confidence: 64%